Peningkatan Kesadaran Lingkungan Peserta Didik melalui Pelatihan Pembuatan Pupuk Organik Cair dari Sampah Dapur - Firna, Lira Firna; Muhammad Ali; Romi Adiansyah (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The training activity for making liquid organic fertilizer from kitchen waste aims to provide understanding and skills for partners regarding the processing of organic waste from kitchen waste into a valuable product by utilizing leftover kitchen ingredients that have only been thrown away. Methodology: In carrying out this training activity on making organic fertilizer from kitchen waste, we use the knowledge sharing method through a service learning approach, namely partners are given an initial understanding of the use of kitchen waste which can be processed into liquid organic fertilizer and partners are guided directly to make liquid organic fertilizer. Results : The results of the implementation of this activity, partners show success, as seen from the increase in understanding and enthusiasm of partners in thoroughly following each stage of implementation. Conclusion : It can be concluded that with this activity partners can find out how to use and process kitchen waste into liquid organic fertilizer which can be used on medicinal plants and vegetables so that in the future they can use household waste. Limitations : There are several challenges and obstacles in implementing this training activity, one of which is the delivery of theory which is quite difficult to understand due to a lack of basic understanding of liquid organic fertilizer so partners need sustainable practice, however Contribution : Carrying out this activity is able to build and encourage an entrepreneurial spirit in Mts Sinoa students or target partners in supporting the goals of the sustainable development program or SDGs in points three and four, namely healthy and prosperous lives and quality education so that they are able to be useful.